The Effects of Polystyrene Microplastics and Copper Ion Co-Contamination on the Growth of Rice Seedlings - Huiyu Jin; Guohe Lin; Mingzi Ma; Lin Wang; Lixiang Liu (Nanomaterials)
Microplastics (MPs) are emerging pollutants of global concern, while heavy metals such as copper ions (Cu2+) are longstanding environmental contaminants with well-documented toxicity. This study investigates the independent and combined effects of polystyrene microplastics (PS-MPs) and Cu on the physiological and biochemical responses of rice seedlings (Oryza sativa L.), a key staple crop. Hydroponic experiments were conducted under four treatment conditions: control (CK), PS-MPs (50 mg·L−1), Cu (20 mg·L−1 Cu2+), and a combined PS-MPs + Cu treatment. The results showed that PS-MPs had a slight stimulatory effect on root elongation, while Cu exposure mildly inhibited root growth. However, the combined treatment (PS-MPs + Cu) demonstrated no significant synergistic or additive toxicity on growth parameters such as root, stem, and leaf lengths or biomass (fresh and dry weights). Both PS-MPs and Cu significantly reduced peroxidase (POD) activity in root, stem, and leaf, indicating oxidative stress and disrupted antioxidant defenses. Notably, in the combined treatment, PS-MPs mitigated Cu toxicity by adsorbing Cu2+ ions, reducing their bioavailability, and limiting Cu accumulation in rice tissues. These findings reveal a complex interaction between MPs and heavy metals in agricultural systems. While PS-MPs can alleviate Cu toxicity by reducing its bioavailability, they also compromise antioxidant activity, potentially affecting plant resilience to stress. This study provides a foundation for understanding the combined effects of MPs and heavy metals, emphasizing the need for further research into their long-term environmental and agronomic impacts.